Analisis Higiene Sanitasi dan Keamanan Makanan Jajanan di Pasar Besar Kota Malang - Galang Panji Islamy; Sri Sumarmi; Farapti Farapti (Amerta Nutrition, 2018)
Background: Food snacks might contain a hazard for consumption, because health problems can be caused by food snacks. Based on SIKer of BPOM showed that 29 incident of food poisoning found in January-March 2014. That incident caused by consuming 5 food snacks. Food snacks are the kind of food being sold in pavement, roadside, station, market, residential area and the site of its kind.Objective: This research was to know the description of food snack from the aspect of food safety in Pasar Besar Malang.Methods:This research was an observational research using descriptive analysis. Samples were taken using the non-probability sampling with the method of purposive sampling, by involving food hawkers at the Pasar Besar Malang. The number of samples consists of 20 vendors. The data collected by the method ofinterview, observation and laboratory test.Results: The results showed all vendors i.e. 20 people were freed from respiratory disease, 17 people (85%) did not wear aprons and headgear when selling, most of the traders 17 people (85%) did not smoking, all food vendor did not get used to scratch the body near the food and all the vendors have to wear gear in serving food, neat and clean clothes, and provide decent sweeties. All vendors did not get used to wash hands. The study found there are 17 vendors who serve food snack did not use a sealed container. Results of microbiologi test showed that the food did not find E.coli in categorizedfood samples. Most of the total samples of the food snack (84%) were categorized as safe food.Conclusion: The study concludes that the hygiene of food handler especially in wearing the apron and hand-washing habits needs to be improved. The way how food to be served needs to be improved, i.e. the necessity to use a sealed container for food snacks. Food safety of packaging snacks is quite good because it has met the minimum requirement as safe foods because not found of E. Coli microbiologic. Vendor should be suggested to wear aprons and must maintain the cleanliness of the hand at the time of selling to avoid contamination at food snacks.ABSTRAKLatar Belakang: Konsumsi makanan dapat berbahaya bagi kesehatan, karena makanan dapat menjadi sumber penularan maupun penyebab dari masalah kesehatan. Sentra Informasi Keracunan (SIKer) Nasional Badan POM (2014) menunjukkan bahwa kejadian keracunan akibat pangan pada bulan Januari-Maret 2014 terdapat 29 insiden. Sebanyak 5 insiden keracunan akibat mengkonsumsi pangan jajanan. Makanan jajanan merupakan makanan yang dijual di kios kaki lima, pinggiran jalan, di tempat umum, tempat pemukiman serta lokasi lain sejenis.Tujuan: Mengetahui gambaran makanan jajanan dari aspek keamanan makanan di Pasar Besar Kota Malang.Metode: Penelitian ini merupakan jenis penelitian deskriptif dengan menggunakan metode pendekatan kualitatif berupa observasi, wawancara dan uji laboratorium. Sampel diambil dengan metode purposive sampling, sebanyak 20 pedagang makanan jajanan di Pasar Besar Kota Malang.Hasil: Hasil penelitian menunjukkan semua pedagang yaitu 20 tidak membiasakan menggaruk badan dekat makanan dan semua pedagang telah memakai perlengkapan dalam menyajikan makanan, menggunakan pakaian yang bersih atau layak pakai, dan membawa alat pembersih keringat. Semua pedagang masih belum membiasakan cuci tangan. Terdapat 15 pedagang yang menyajikan jajanan tidak menggunakan wadah tertutup. Hasil uji mikrobiologi E. Coli, tidak ditemukan E. Coli pada semua sampel makanan yang diperiksa.Kesimpulan: hygiene dari penjual perlu diperbaiki, khususnya memakai celemek dan cuci tangan. Keamanan makanan jajanan sudah baik karena tidak ditemukan mikrobiologi bakteri E. Coli. Pedagang sebaiknya mengupayakan untuk selalu memakai celemek dan harus menjaga kebersihan tangan.